(untitled) (Journal of Science and Technology, 2016)
Food markets serve as important indicators of the state of an economy due to their ability to direct resource allocation through the pricing mechanism. Prices alone however fail to reflect the proper signals if the process of price formation and the resulting market prices are assumed to be complete indicators of current and future market conditions without the cognizance of the specific environmental constraints and opportunities that characterize the marketing system. The correlation co-efficient of market prices or its contemporary modifications remains one of the most popular methods of assessing market performance. However, such tools can yield misleading results if applied across spatial markets with a non-homogenous harvesting period or market infrastructure, but a common trading market. In analyzing the performance of the maize market in Ghana from a heuristic standpoint, the paper attempts to highlight some pitfalls which might be obscured when the correlation co-efficient, as a measure of market performance, is interpreted without due consideration of the peculiarities of the marketing system involved.